Horizontal ridge augmentation of the atrophic anterior maxilla using rhBMP-2/ACS or autogenous bone grafts: A proof-of-concept randomized clinical trial - Freitas, Rubens Moreno de [UNESP]; Susin, Cristiano; Spin-Neto, Rubens [UNESP]; Marcantonio, Claudio [UNESP]; Wikesjö, Ulf M. E.; Pereira, Luís Antônio Violin Dias; Marcantonio Júnior, Elcio [UNESP] (Wiley, 2013)
Aim To compare the effect of recombinant human bone morphogenetic protein-2 (rhBMP-2) in an absorbable collagen sponge carrier (ACS) with autogenous bone graft for augmentation of the edentulous atrophic anterior maxilla. Methods Twenty-four subjects were enrolled in a randomized, controlled, parallel-group, open-label clinical trial. Subjects either received rhBMP-2/ACS (1.5 mg/ml) or particulated autogenous bone harvested from the mandibular retromolar region. A titanium-mesh was used to provide space and wound stability. A guide was used to standardize clinical recordings using an analogue caliper. Alveolar ridge width was also assessed using cone-beam computed tomography. Results rhBMP-2/ACS yielded significantly greater radiographic horizontal bone gain compared with autogenous bone graft at immediate subcrestal levels (1.5 ± 0.7 versus 0.5 ± 0.9 mm; p = 0.01); non-significant differences were observed at mid- (2.9 ± 0.8 versus 2.9 ± 0.9 mm; p = 0.98) and apical (1.7 ± 0.9 versus 1.8 ± 1.1 mm; p = 0.85) crestal levels. No significant differences in clinical horizontal bone gain were observed at 6 months between rhBMP-2/ACS and autogenous bone graft (3.2 ± 0.9 mm versus 3.7 ± 1.4 mm; p = 0.31). Sixty-two implants were placed after 6 month of healing with no significant differences between groups for number of implants, implant size, primary stability and survival. Conclusions rhBMP-2/ACS appears a realistic alternative for augmentation of the edentulous atrophic anterior maxilla. © 2013 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.
Keywords: alveolar ridge augmentation; autogenous bone graft; randomized-controlled trial; recombinant human bone morphogenetic protein; rhBMP-2